2001
DOI: 10.4067/s0717-71782001000100001
|View full text |Cite
|
Sign up to set email alerts
|

Morfometría comparada de los estatolitos del calamar Loligo gahi d'Orbigny, 1835 (Cephalopoda: Loliginidae) del norte de Perú e islas Falkland

Abstract: Recibido: 19 noviembre 1999; versión corregida: 14 julio 2000; aceptado: 2 noviembre 2000RESUMEN. Se analizó un total de 241 estatolitos: 141 pertenecientes a Loligo gahi del norte del Perú (70 estatolitos izquierdos y 71 derechos) correspondientes a 34 machos y 47 hembras, y 100 de las islas Falkland (50 estatolitos izquierdos y 50 derechos) correspondientes a 35 machos y 23 hembras. En cada estatolito se midió longitud total (LT), longitud del domo (LD) y longitud del rostro (LR), determinándose en cada ejem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…The second study used discriminant analysis to investigate the differences in statolith morphometric measurements between samples from Northern Peru and the Falkland Islands. There was significant sexual dimorphism in both regions and significant differences between regions for individuals of the same sex (Vega et al 2001). The third study found significant differences in linear morphometric body measurements between specimens collected in Peru, Southern Chile and the Falkland Islands, as well as a greater sexual dimorphism in specimens collected from Falkland Islands waters compared to the other two geographic locations (Vega et al 2002).…”
mentioning
confidence: 96%
“…The second study used discriminant analysis to investigate the differences in statolith morphometric measurements between samples from Northern Peru and the Falkland Islands. There was significant sexual dimorphism in both regions and significant differences between regions for individuals of the same sex (Vega et al 2001). The third study found significant differences in linear morphometric body measurements between specimens collected in Peru, Southern Chile and the Falkland Islands, as well as a greater sexual dimorphism in specimens collected from Falkland Islands waters compared to the other two geographic locations (Vega et al 2002).…”
mentioning
confidence: 96%
“…Es posible que la variabilidad intraespecífica de los índices tenga una componente sexual ya que el dimorfismo sexual, en las estructuras duras, entre machos y hembras, ya había sido descrito anteriormente (Bolstad, 2006;Vega, 2010;CrespiAbril et al, 2010). En este estudio, la muestra analizada incluyó ejemplares tanto de sexo masculino, como femenino, excepto en aquellos casos en los cuales se contó con un ejemplar, que con excepción de Neorossia aff.…”
unclassified
“…In studies of trophic ecology, statoliths are found in the stomach content of predatory species of fish and cephalopods. They are used for identification purposes (Clarke and Fitch 1975;Clarke 1978;Vega et al 2001). The morphological description of statoliths allows the identification of the prey species.…”
Section: Introductionmentioning
confidence: 99%
“…The morphological description of statoliths allows the identification of the prey species. In addition, statolith morphometrics can be used to identify and compare subpopulations (Vega et al 2001;Schwarz and Perez 2007). This highlights the value of the statoliths as taxonomic tools (Clarke 1978;Brunetti and Ivanovic 1991;Flores and Garland 2002).…”
Section: Introductionmentioning
confidence: 99%